Discovery of METTL3 Small Molecule Inhibitors by Virtual Screening of Natural Products - Du, Yue; Yuan, Yongliang; Xu, Le; Zhao, Fang; Wang, Wenbin; Xu, Yiping; Tian, Xin (Frontiers in Pharmacology, 2022)
N6-methyladenosine (m6A) is the most prevalent mRNA modification in mammalian cells that is mainly catalyzed by the methyltransferase complex of methyltransferase-like 3-methyltransferase-like 14 (METTL3-METTL14). Many lines of evidence suggest that METTL3 plays important roles in various of diseases such as cancers and viral infection. In the present study, 1042 natural products from commercially available sources were chosen to establish a screening library, and docking-based high-throughput screening was performed to discover potential METTL3 inhibitors. The selected compounds were then further validated by an in vitro methyltransferase inhibition assay in which m6A content was determined by LC-MS/MS. A cellular assay of the inhibition of m6A methylation was performed to determine the METTL3 inhibitory activity of the selected compound. CCK-8 assay was applied to evaluate the effects of the selected compound on tumor cell viability. Additionally, binding mode analysis, molecular dynamics (MD) simulation and binding free energy analysis were performed to study the process and characteristics of inhibitor binding. Finally, quercetin was identified as a METTL3 inhibitor with an IC50 value of 2.73 μM. The cellular assay of m6A methylation inhibition showed that quercetin decreased m6A level in a dose-dependent manner in MIA PaCa-2 pancreatic cancer cells. CCK-8 assay showed quercetin efficiently inhibited the proliferation of MIA PaCa-2 and Huh7 tumor cells, with IC50 values 73.51 ± 11.22 μM and 99.97 ± 7.03 μM, respectively. Molecular docking studies revealed that quercetin filled the pocket of the adenosine moiety of SAM but not the pocket of the SAM methionine in the METTL3 protein, and hydrogen bonds, hydrophobic interactions and pi-stacking were formed. The values of the root mean square deviation (RMSD), the root mean square fluctuations (RMSF) and binding free energy suggested that quercetin can bind efficiently to the pocket of the METTL3 protein and formed a stable protein-ligand complex. The present study is the first to identify METTL3 inhibitors from natural products; thus, providing a basis for subsequent research and facilitating the development of METTL3-targeting drugs for diseases.